“Defendendo” a sociedade: um estudo sobre as trajetórias de oito juízes - Ricardo Visser; Gustavo Siqueira (Ciências Sociais Unisinos)
This study aims the analysis of the social trajectory of eight judges of two judicial authorities. In order to do so, we concentrated ourselves on three main analytical dimensions: a) firstly, we addressed their social origin through the familial milieu; b) we then investigated their narratives on the civil service examination and professional expectations; c) we finally analyzed their stances on national politics and current public policies. Taking into account quantitative data and also our qualitative research, it was observed that there is a correspondence between both analytical levels which leads to the perception that judges are mainly recruited in the middle and upper middle classes. Taking them as observers of national politics and public policies, we do not intend to reconstruct the political “mentality” of the judges, but to indicate a persisting pattern in their discourses and standpoints. Lastly, in relation politics and public policies, we argue that interviewed judges are oriented by a savant common sense which is rarely capable of self observation.